2017
DOI: 10.1021/jacs.7b05007
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Reactivity of TrpB: A General Biocatalytic Platform for Synthesis of Tryptophan Analogues

Abstract: Derivatives of the amino acid tryptophan (Trp) serve as precursors for the chemical and biological synthesis of complex molecules with a wide range of biological properties. Trp analogs are also valuable as building blocks for medicinal chemistry and as tools for chemical biology. While the enantioselective synthesis of Trp analogs is often lengthy and requires the use of protecting groups, enzymes have the potential to synthesize such products in fewer steps and with the pristine chemo- and stereoselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 46 publications
1
150
1
Order By: Relevance
“…Many substituted indoles and even other amino acids can participate in this versatile reaction, which affords access to complex starting materials for downstream modification . Recently, these efforts have been made even easier by evolving the β‐subunit of tryptophan synthase (TrpB; EC 4.2.1.20) for efficient stand‐alone function . These engineered TrpBs can operate at high temperatures, which is helpful in solubilizing hydrophobic indoles, and provide access to highly complex Trp analogues in good yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many substituted indoles and even other amino acids can participate in this versatile reaction, which affords access to complex starting materials for downstream modification . Recently, these efforts have been made even easier by evolving the β‐subunit of tryptophan synthase (TrpB; EC 4.2.1.20) for efficient stand‐alone function . These engineered TrpBs can operate at high temperatures, which is helpful in solubilizing hydrophobic indoles, and provide access to highly complex Trp analogues in good yield.…”
Section: Methodsmentioning
confidence: 99%
“…To test the promiscuity of Rgn TDC, we sought to measure its kinetic parameters with a complete set of 4‐, 5‐, 6‐, and 7‐chlorotryptophans; however, the requisite enantiopure chlorotryptophans were not readily available. We therefore prepared each Trp analogue from its indole precursor through a simple biocatalytic reaction by using engineered TrpBs from Pyrococcus furiosus with high stand‐alone activity . Surprisingly, the kinetic parameters of Rgn TDC with each chlorotryptophan showed only modest decreases in catalytic efficiency when compared to the native Trp substrate (Table , Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymes can perform enantio‐ and regioselective chemistry in the presence of reactive moieties such as primary amines, obviating the need for expensive and intricate chiral catalysts, chiral separations, and protecting groups. To this end, our lab previously reported the directed evolution of the tryptophan synthase β‐subunit (TrpB) as a stand‐alone biocatalytic platform for the synthesis of diverse tryptophan analogues (Scheme B) . Herein, we report a simple, efficient route for the synthesis of AzAla from stable, commercially available starting materials by using an engineered TrpB (Scheme C).…”
Section: Methodsmentioning
confidence: 99%
“…The significant effect of the E104(105)G mutation suggested that this conserved catalytic residue might be playing an important role in the non‐native azulene reaction. We explored this possibility by examining two engineered variants with and without the E104(105)G mutation: Pf 5G8, which exhibits optimal activity at 75 °C, and Tm 9D8*, which exhibits optimal activity at lower temperatures such as 37 °C . Challenging the enzymes with indole demonstrated that this mutation only modestly decreases the rate of Trp formation (Figure ), with an additional slight decrease in the chemoselectivity of the reaction that leads to the formation of trace amounts of isoTrp (a product of the N‐alkylation of indole, shown in Figure S2 and described previously).…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] We performed analytical biotransformations with 11 representative nucleophiles with three β-branched amino acid substrates, yielding 27 tryptophan analogs, 20 of which are previously unreported (Table 2). Each reaction was analyzed by liquid-chromatography/mass spectrometry (LCMS) and TTN were calculated by comparing product and substrate absorption at the isosbestic wavelength (Table S4).…”
Section: B9mentioning
confidence: 99%